2009
DOI: 10.1002/jgm.1367
|View full text |Cite
|
Sign up to set email alerts
|

A systematic study of the function of the human β‐globin introns on the expression of the human coagulation factor IX in cultured Chinese hamster ovary cells

Abstract: Potentials of hBG introns as enhancer-like elements for the expression of the hFIX in cultured CHO cells and a higher activity with respect to the second hBG intron compared to the first one were demonstrated. The larger number of TFBs in the second hBG intron reflects its stronger effect. The results obtained suggest possible synergistic functions of the hBG introns and Kozak on the expression level of hFIX in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 42 publications
1
22
1
Order By: Relevance
“…Secondly, the probable function of the hBG intron-II within the coding region of hFIX-cDNA was also examined. In contrast to our previous results (Haddad-Mashadrizeh et al 2009), application of the hBG intron-II in this study, in a similar position but under a different regulation system caused a dramatic reduction in the expression levels of the hFIX. Based on the results obtained from RT-PCR, the transcript precursors of the hFIX-II minigene in the cells carrying the prABE/CMV.FIX-II plasmid, are not properly spliced, which may explain the low expression levels of the hFIX by the intron-containing hFIX minigenes in the cultured HepG2 cells.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Secondly, the probable function of the hBG intron-II within the coding region of hFIX-cDNA was also examined. In contrast to our previous results (Haddad-Mashadrizeh et al 2009), application of the hBG intron-II in this study, in a similar position but under a different regulation system caused a dramatic reduction in the expression levels of the hFIX. Based on the results obtained from RT-PCR, the transcript precursors of the hFIX-II minigene in the cells carrying the prABE/CMV.FIX-II plasmid, are not properly spliced, which may explain the low expression levels of the hFIX by the intron-containing hFIX minigenes in the cultured HepG2 cells.…”
Section: Discussioncontrasting
confidence: 83%
“…It was previously shown that the hFIX intron-I could enhance expression of FIX transgene in vitro (Kurachi et al 1995). In our previous study, we introduced hBG intron-II in the second intronic position of the hFIXcDNA and observed 500% increase of expression level relative to that of the intron-less hFIX-cDNA in vitro (Haddad-Mashadrizeh et al 2009). Improvements of transgene expressions by application of the hBG intron-II in a number of expression systems have also been shown (Harding et al 2004;Palmiter et al 1991).…”
Section: Introductionmentioning
confidence: 93%
“…Several different introns have been tested for intron mediated enhancement in gene therapy vectors so far and the results show a clear benefit from the additional sequences. Transgenic mice have shown an almost 5-fold increase in the production of human thrombopoietin upon inclusion of only a single intron of the same gene (191) and introns of mouse, rabbit and human β-globin have been shown to be potent enhancer elements (192, 193). Several viral introns including SV40 (194) or CMV (195) have also been tested in vitro and in vivo more or less successfully.…”
Section: Vector Engineeringmentioning
confidence: 99%
“…With several post-translational modifications, mostly necessary for its biological activity, this protein preferably requires to be expressed in mammalian cells [8,11]. Different mammalian expression systems, including Chinese hamster ovary (CHO) and baby hamster kidney (BHK) cells, which provide post-translational modifications similar to that of human cells, have been reported to be used for production of functional rhFIX [8,11,12].…”
Section: Introductionmentioning
confidence: 99%